ANALISIS TEKNIK PENGAMBILAN KEPUTUSAN PADA LEMBAGA PENDIDIKAN - Ayu Nur Chamidah; Ahmad Manshur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Decision-making is a crucial aspect of the educational field as it directly affects learning quality, school management, and the achievement of educational goals. This article aims to describe various decision-making techniques applicable within educational institutions and to analyze the factors influencing the effectiveness of decisions made by school principals and teachers. The research method used is library research, collecting data from various literatures, academic journals, and online sources related to the concept and application of decision-making techniques. The results indicate that the success of decision-making in schools depends on the accuracy of the techniques applied, such as rational, intuitive, participatory, and data-driven approaches. Participatory and group decision-making techniques foster collaboration and shared responsibility, while rational and data-driven techniques enhance the objectivity of educational policies. Therefore, effective decision-making in education must be systematic, democratic, and data-based to support the development of adaptive, efficient, and sustainable educational management.